You wouldn't want to be a worker on the Statue of Liberty : a monument you'd rather not build - Malam, John, 1957- (You wouldn't want to--, 2009)
"Get ready...as a young French sculptor, you're about to embark on one of the most ambitious artistic projects of the 19th century. There's not a moment's rest for a worker on the Statue of Liberty..."--Cover back.